Pengaruh Kepercayaan Diri, Penguasaan Materi Dan Keterampilan Berkomunikasi Terhadap Kemampuan Public Speaking Mahasiswa Pendidikan Agama Islam IAIN Curup - Maharani, Mega Selvi (Edification Journal : Pendidikan Agama Islam, 2025)
Public speaking difficulties for students are often caused by nervousness, material readiness and grammar.  This study aims to find out: the influence of self-confidence, material mastery, communication skills, on public speaking skills. This study focuses on the significant influence of each, simultaneously and the amount of contribution of the influence of predictors (independent variables) on bound variables. This survey was given to Islamic Religious Education students at the Curup State Islamic Institute Class of 2021 using a questionnaire. Data analysis was carried out using regression analysis. The results showed that: (1) There was a significant influence between confidence (X1) and material mastery (X2) on public speaking ability (Y), but there was no significant influence of communication skills (X3) on public speaking ability (Y). Simultaneously, there is a significant influence of confidence, material mastery, communication skills on public speaking and these three variables contribute 95% to the variables of public speaking ability. By knowing this, it is hoped that students can increase their confidence and mastery of the material when making presentations in front of the class and outside the classroom.